Legal Aspects of Organ Transplant - Avendaño Hübner, Jorge (1974)
The aim of this paper is to examine the legal aspects related to organ transplantation. For this purpose, the Health Code will be analyzed, highlighting the most problematic aspects of organ donation and providing a more consistent interpretation for its application. In addition, the different types of death and their relation to organ donation are developed. It is concluded that the definition of death is a problem of great importance because of its legal consequences.